Trembesi Digestibility Fermented By Lactobacillus Plantarum Mut 7 - Ahimsa Kandi Sariri; Sri Sukaryani (Bantara Journal of Animal Science, 2020)
The specific purpose of this third year research is to study the level of digestibility in vivo BTTF and BTF and to study the effect of the use of tamarind leaves by the method of increasing the quality of nutrient content and decreasing saponin in PO cattle feed (ongole breeds). The specific target of the third year is BTTF and BTF in vivo digestibility. This study was designed with a Completely Randomized Directional Design with two treatments, namely in vivo digestibility BTTF and BTF. From this study it can be concluded that the level of digestibility in vivo from BTF was 53.33% and was significantly different from BTTF. Keywords: in vivo digestibility, trembesi